Lupus-Associated Pulmonary Arterial Hypertension: Variable Course and Importance of Prompt Recognition - Kofi A. Mensah; Rajwardhan Yadav; Terence K. Trow; Cristina M. Brunet; Wassim H. Fares (Case Reports in Medicine, 2015)
We describe a critically ill young woman with systemic lupus erythematosus (SLE) presenting with circulatory shock, multiorgan dysfunction, and elevated right-sided heart pressures. She was found to have recurrent acute severe pulmonary arterial hypertension (PAH) in the setting of an SLE flare. Our report highlights the variable course that SLE-associated PAH can take in the same patient and the implications of this for instituting the most effective treatment approach with each episode. This report also highlights the potential for SLE-associated PAH to present with life-threatening symptoms requiring critical care level interventions. We also describe evidence-based therapies, which can result in significant improvement in symptoms, function, and long-term outcomes.